Apgar Score in Term Pregnancies with Isolated Oligohydramnios - TASHHIR RANA, ALIA NASEER UD DIN, SALEHA ANWER, BUSHRA BANO (Journal of Fatima Jinnah Medical University, 2018)
Oligohydramnios is defined as amniotic fluid index (AFI) < 5th centile for the gestational age. AFI < 5cm or maximum vertical pocket devoid of umbilical cord or fetal limbs measures < 30cm, in the presence of intact membrane. It is well established that oligohydramnios is associated with a high risk of adverse perinatal outcomes, On the other hand, oligohydramnios is a poor predictor for adverse outcome and leads to un-necessary inductions and followed by increased caesarean sections rate. Objective: To determine the frequency of adverse perinatal outcome in pregnancies with isolated oligohydramnios at term. Study design: Case Series. Settings: The study was carried out in the Department of Obstetrics & Gynaecology unit IV, Sir Ganga Ram Hospital, Lahore. Duration of Study: From 30th September 2012 to 29th March 2013 Results: Majority of the patients i.e. 43.5%(n=87) were between 20-25 years old, mean and SD was calculated as 28.43+4.27 years. 38%(n=76) were between para 1-2, 41.5%(n=83) were para 3-4, while 20.5%(n=41) were para >4. Frequency of perinatal outcome reveals that apgar score <6 at 1 minute was calculated in 10.5%(n=21) and <7 at 5 minutes in 8.5%(n=17) which is not very significant. Conclusion: Isolated oligohydramnios is not associated with adverse perinatal outcome.